Indicadores poblacionales en caninos y felinos y existencias de otras especies domésticas en la comuna de El Bosque, Región Metropolitana, Chile - Ibarra M., Luis; Cisternas L., Paola; Valencia G., Jorge; Morales M., María A. (Avances en Ciencias Veterinarias, 1997)
In order to know dog and cat population indexes and the existences of other species a survey in a random sample of 599 households was done in the county El Bosque. The population size was estimated in 41,586 dogs, with 1.01 dog per house and a dog human ratio of 4.14:1. The mean age of dog population was 2.63 years, the sex ratio was 1.91 male: 1 female, the breed ratio was 3.67 mixed: 1 pure breed. The estimated cat population was 18,170, with 0.44 cats per house and a cat human ratio of 9.5:1. Other animals were present in 16,4% of the households, being the domestic and ornamental birds the most frequent. Key words: demography, canine population, feline, population Palabras clave: demografía, población canina, población felina.